Verification of authenticity and fraud detection in South African honey using NIR spectroscopy. (March 2017) - Guelpa, Anina; Marini, Federico; du Plessis, Anton; Slabbert, Ruhan; Manley, Marena
Abstract: The South African honey industry will benefit from a reliable method that can verify authenticity as well as detect fraudulence of honey that is on the market. This work presents the use of near-infrared (NIR) spectroscopy in combination with chemometrics as a fast and relatively inexpensive method to discriminate between authentic South African and imported and/or adulterated honey. A supervised chemometric approach was followed on NIR spectra collected from genuine South African honey, as well as intentionally adulterated honeys with sugar solutions (glucose and fructose) and also cheap imported honey. By using partial least squares discriminant analysis (PLS-DA), overall classification accuracies of between 93.3% and 99.9% were obtained when using three different NIR instruments (a laboratory instrument, as well as a portable and a mobile instruments). The usefulness of NIR spectroscopy for accurate honey classifications, regardless the instrument specifications, are demonstrated. Highlights: PLS-DA applied to NIR spectroscopy data verified the authenticity of South African honey. PLS-DA applied to NIR spectroscopy data detected adulteration of South African honey. NIR spectroscopy is advantageous as the measurements are fast, non-destructive and non-invasive. The type of NIR instrument did not compromise classification accuracies.